2013
DOI: 10.1002/htj.21069
|View full text |Cite
|
Sign up to set email alerts
|

Euler‐Lagrangian Simulation of Magnetic Field Effects on the Mixed Convection of Ferrofluid

Abstract: In this article, the hydro‐thermal behavior of a ferrofluid flow (kerosene and 4 vol% Fe3O4) in a vertical tube in the presence of different magnetic field gradients using a two‐phase Euler–Lagrange model and control volume technique has been reported. Two cases for the magnetic field gradients have been considered to affect the mixed convection of the ferrofluid: non‐uniform axial negative and positive field gradients. Unlike our previous studies instead of uniform nanoparticle distribution within the flow, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…His results showed that the effects of a magnetic field are considerable and it can shift the reattachment of the flow in the downstream direction. Recently Aminfar and colleagues [13][14][15][16][17][18][19] and Mohammadpourfard [20] investigated the effects of different nonuniform magnetic fields on the hydrodynamic and thermal behavior of a ferrofluid. They showed the effects of applying a magnetic field on the Nusselt number and the friction.…”
Section: Introductionmentioning
confidence: 99%
“…His results showed that the effects of a magnetic field are considerable and it can shift the reattachment of the flow in the downstream direction. Recently Aminfar and colleagues [13][14][15][16][17][18][19] and Mohammadpourfard [20] investigated the effects of different nonuniform magnetic fields on the hydrodynamic and thermal behavior of a ferrofluid. They showed the effects of applying a magnetic field on the Nusselt number and the friction.…”
Section: Introductionmentioning
confidence: 99%